Culture Management Literature In Realizing Student Achievement At MTsN 3 Pamekasan - Hurriyatul Ifadhah; Hilmi Qosim Mubah (Aqlamuna: Journal of Educational Studies, 2023)
Literacy culture management is an ability to manage, organize, mobilize, and control positive values ​​in carrying out thinking habits through readi ng and writing activities. Literacy culture is very supportive of the formation of students who can achieve achievement. So that if the literacy culture can be managed properly, the literacy culture that is built can realize efficient student achievements. Planning a literacy culture in realizing student achievement at MTSN 3 Pamekasan is the desire to create a literacy culture madrasa with discussions. The implementation of literacy culture in realizing student achievement at MTSN 3 Pamekasan is to be carried out every day with a predetermined time. Evaluation of literacy culture in realizing student achievement at MTSN 3 Pamekasan is by the existence of several supporting factors and inhibiting factors as well as solutions used to implement culture literacy that can realize student achievement.